Analysis of methanol and organometallic MnO2 fuels as alternative fuels in a diesel engine - Hazar, Hanbey; Temizer, Ilker (Taylor & Francis Ltd, 2014)
In this study, methanol and organometallic MnO2 fuels were used to improve the properties of diesel fuel. In addition, the effect of methanol fuel on engine oil and a piston ring was also examined experimentally in a four-cylinder, direct injection diesel engine running at 200 bar. Three different diesel fuels were prepared by adding 5, 10 and 15% methanol to diesel fuel. In order to prevent phase separation, 1% dodecanol was added to the mixture. Organometallic compounds of manganese were synthesised to prepare the solutions. The most effective amount and performance of anti-freeze were determined. From the results, it was observed that carbon monoxide emissions decreased and NOx emissions increased with the increase in the amount of methanol. On the other hand, organometallic MnO2 increased the cetane number and decreased the freezing point, viscosity and flame temperature.
Keywords: organometallic MnO2; methanol; dodecanol; diesel engine; exhaust emissions